Hepatitis C virus infection: early diagnosis and identification of response to antiviral therapy. (1st September 2001) - Bonino, Ferruccio; Colombatto, Piero; Civitano, Luigi; Coco, Barbara; Oliveri, Filippo; Brunetto, Maurizia R
Early diagnosis of hepatitis C infection and early identification of virologic response to antiviral therapy represent major hallmarks of the quality of a case. They contribute to reducing the risk of hepatitis C infection from blood product and improve disease management in patients treated with antivirals. Some of the current issues and perspectives involved in detection and quantification of viral load during the incubation phase of infection and monitoring the early phase of antiviral therapy are discussed.